Community Visioning Programs : Processes and Outcomes. - Walzer, Norman (Community development research and practice series., 2012)
Community visioning is key in helping local public officials and community leaders create a flourishing future for their cities, and is essential for the effective planning and implementation of these strategies. Visioning involves collaborative goal setting to motivate actions -- of planners, citizens, and officials -- in order to design and carry out a strategic planning process for the successful development of the community. The use of visioning since the 1980s has led to a wealth of information on the productivity of the paths it has taken. The contributors, all with experience working in.